Heat Integration of Material Transfer Streams in Batch Processing Plants - J.-Y. Lee; E.R. Seid; M. Majozi (Chemical Engineering Transactions, 2015)
Batch processes are flexible allowing the production of different products within the same facility, and suitable for producing low volume, high value-added products such as pharmaceuticals and agrochemicals. The trend towards batch processing has necessitated the development of scheduling techniques. In addition to process scheduling, heat integration has been increasingly considered for batch plants to reduce external utility (e.g. steam and cooling water) requirements for tasks involving heating or cooling, such as endothermic and exothermic reactions. In this work, a mathematical technique for simultaneous process scheduling and heat integration of batch plants is presented. The formulation, based on a superstructure, aims to maximise the coincidence of availability of hot and cold process stream pairs with feasible temperature driving forces, whilst taking into account scheduling constraints. Heat integration during stream transfer can shorten the time required for heating and cooling in processing units, and is expected to enable higher production and lower utility consumption for batch plants. A case study is solved to demonstrate the application of the proposed mathematical model.